2018
DOI: 10.1084/jem.20172310
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral PDGFRα+gp38+ mesenchymal cells support the differentiation of fetal liver–derived ILC2

Abstract: We demonstrate that the quantity of IL-7 and Notch signaling differentially regulate lymphocyte fate. We also identify ILC progenitor and immature ILC2 in the fetal mesentery, which are terminally differentiated and matured by PDGFRα+gp38+ mesenchymal cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
86
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(93 citation statements)
references
References 66 publications
7
86
0
Order By: Relevance
“…Accordingly, the presence of all human ILC subsets in the lung has been described in the fetus already by gestational week 14 . Although similar data, analyzing the full ILC profile in the murine fetal lung have yet to be published, pulmonary ILC2 have been shown to be present in low numbers at embryonic day 18 . Remarkably, the upregulation of lung IL‐33 in neonatal mice upon the trauma of the first breath was described to coincide with an emerging wave of IL‐13‐producing ILC2 in the lung, shaping the pulmonary immune environment from birth to adult .…”
Section: Ilcs In the Lungmentioning
confidence: 90%
“…Accordingly, the presence of all human ILC subsets in the lung has been described in the fetus already by gestational week 14 . Although similar data, analyzing the full ILC profile in the murine fetal lung have yet to be published, pulmonary ILC2 have been shown to be present in low numbers at embryonic day 18 . Remarkably, the upregulation of lung IL‐33 in neonatal mice upon the trauma of the first breath was described to coincide with an emerging wave of IL‐13‐producing ILC2 in the lung, shaping the pulmonary immune environment from birth to adult .…”
Section: Ilcs In the Lungmentioning
confidence: 90%
“…Human ILC2s are capable of producing IL‐4, IL‐5, IL‐6, IL‐8, IL‐9, GM‐CSF, and amphiregulin in response to IL‐2 + IL‐33 . Moreover, a recent study showed that mouse ILC2s in the mesentery of the fetus and newborn are unable to respond to IL‐33 without co‐stimulatory cytokines while ILC2s in adult mesentery respond to IL‐33 alone …”
Section: Activating Cytokines (Il‐33 and Il‐25)mentioning
confidence: 99%
“…In addition, a Lin − CD127 + ILC that expresses chemoattractant receptor homologous molecule expressed on Th2 lymphocytes (CRTH2) and natural killer cell marker CD161 populates the fetal gut and responds to IL‐25 and IL‐33 to produce type 2 cytokines . In mice, fetal gut Arginase‐1 + Id2 + ILC precursors have the capacity to differentiate into ILC1s, ILC2s, and ILC3s, and the ILC2 development is supported by mesenteric platelet‐derived growth factor receptor α (PDGFRα) + glycoprotein‐38 (gp38) + mesenchymal cells . In a recent study, Koning and colleagues identified a Lin − CD7 + CD127 − CD45RO + CD56 + population by mass cytometry in human fetal intestine could develop into CD45RA + NK cells and CD127 + RORγt + ILC3s .…”
Section: Tissue‐related Control Of Ilc Maturation and Functionalitymentioning
confidence: 99%